Middle market M & A : handbook for advisors, investors, and business owners - Marks, Kenneth H.; Blees, Christian W.; Nall, Michael R.; Stewart, Thomas A., 1948- (Wiley finance series., 2023)
Formula Definitions -- Part 3 The M&A Practice and Processes -- Chapter 6 Practice Management -- Primary M&A Advisors -- Marketing the M&A Practice -- Target Audience -- Networking -- Marketing and Advertising -- Pretransaction Consulting -- Valuation Services -- Other Consulting Services -- Becoming an Expert -- Client Acceptance -- Confidentiality -- Client Engagement -- Identification of the Parties -- Scope of Service -- Limitations and Disclosures -- Fees-Selling Advisor -- Example Fee Structures -- Termination and Tail -- Buy-Side Engagements